2006
DOI: 10.2136/sssaj2005.0259
|View full text |Cite
|
Sign up to set email alerts
|

Rate‐Limited Boron Transport in Soils: The Effect of Soil Texture and Solution pH

Abstract: Although boron (B) adsorption significantly depends on soil texture and pH, few attempts have been made to estimate their influence on B transport behavior. Adsorption and transport of B in three soils of different textures were investigated in batch and column experiments. The B adsorption on the soils in batch experiments was rapid and an apparent adsorption equilibrium was reached over the first several hours. The extent of adsorption on each of the soils was strongly dependent on pH, increasing sharply as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
0
17
1
7
Order By: Relevance
“…Silva et al (1995) studied B leaching in an Ultisol under cotton and reported that the nutrient reached a depth of 60 cm after nine years of annual borax application in the sowing furrow. While B mobility is favored by acidic conditions, the movement of the element in deeper layers is related to the application time and rate, initial concentration of the element (Rosolem & Biscaro, 2007), quantity of percolated water (Patil et al, 1997;Communar & Keren, 2006 and magnitude of soil absorption. Azevedo et al (2001) affirm that B absorption directly correlates with organic material content, specific clay surface, presence of kaolinite, and exchangeable Al.…”
Section: Boron Concentration In Relation To Soil Depthmentioning
confidence: 99%
See 2 more Smart Citations
“…Silva et al (1995) studied B leaching in an Ultisol under cotton and reported that the nutrient reached a depth of 60 cm after nine years of annual borax application in the sowing furrow. While B mobility is favored by acidic conditions, the movement of the element in deeper layers is related to the application time and rate, initial concentration of the element (Rosolem & Biscaro, 2007), quantity of percolated water (Patil et al, 1997;Communar & Keren, 2006 and magnitude of soil absorption. Azevedo et al (2001) affirm that B absorption directly correlates with organic material content, specific clay surface, presence of kaolinite, and exchangeable Al.…”
Section: Boron Concentration In Relation To Soil Depthmentioning
confidence: 99%
“…While acidic conditions encourage B mobility, B movement in depth will be a function of applied rate, application date, initial concentration of the element in the soil (Rosolem & Biscaro, 2007), and quantity of water percolated (Patil et al, 1997;Communar & Keren, 2006.…”
Section: Boron Concentration In Relation To Soil Depthmentioning
confidence: 99%
See 1 more Smart Citation
“…A lixiviação de boro tem sido apontada como uma das causas de deficiência de boro, principalmente em solos arenosos (Silva et al, 1995;Communar & Keren, 2006), como o da área experimental (Tabela 2). Porém, a matéria orgânica, presente nas camadas superiores do solo (Tabela 1), pode ter complexado ou adsorvido parte do boro aplicado (Hatcher et al, 1967) e proporcionado, com o tempo, uma descomplexação ou dessorção, suficiente para atender a demanda da planta.…”
Section: Resultsunclassified
“…Porém, a matéria orgânica, presente nas camadas superiores do solo (Tabela 1), pode ter complexado ou adsorvido parte do boro aplicado (Hatcher et al, 1967) e proporcionado, com o tempo, uma descomplexação ou dessorção, suficiente para atender a demanda da planta. A lixiviação de boro pode ocorrer (Silva et al, 1995;Rosolem & Bíscaro, 2007), todavia é mais freqüente em solos arenosos, pobres em matéria orgânica e localizados em regiões chuvosas (Silva et al, 1995;Communar & Keren, 2006). Segundo Yamada (2000), as razões para não se aplicar doses de boro maiores que as atualmente praticadas são duas: a estreita faixa entre a deficiência e a toxidez de boro na planta e a facilidade de Frémond et al (1966).…”
Section: Resultsunclassified